Analyzing "integral indices" to quantify the effects of a perturbing force over satellites. (November 2019) - de Almeida, A.K.; Bertachini de Almeida Prado, A.F.; Vilhena de Moraes, R.; Lara, M.
Abstract: Integral indices are useful tools to be used to identify characteristics of an orbit. Using analytical solutions for a perturbative version of the Tsien problem (radial low thrust applied to a spacecraft), two indices are defined and evaluated. They can make a map of the orbits disturbed by the thrust. Highlights: Measuring the influence of the perturbation on the trajectory and velocity. Perturbation solution to the Tsien problem - low, constant and radial thrust. Defining useful "integral indices" to be used in astrodynamic problems.